Variabilidade comportamental reforçada negativamente em contingências de fuga com humanos - Silva, Raniel Barbosa de Almeida (2020)
Procedures in which the emission of varied units is required for reinforcement (e.g., Lag n) and in which only units are required, but not variation (Yoked), in whichthereinforcement is released according to the first procedure, indicates control ofbehavioral variability by its consequences. In addition, it has been shown that the levelsof variability may be a function of the levels of variation requirement (e.g., manipulation of parameter n in Lag n). Most of these statements occurred in procedureswith positive reinforcement. However, the literature in which these procedures occurredwith negative reinforcement is sparce. Accentuated fact in the study withhumanparticipants. The present study aimed to answer: a) if the behavioral variabilitycanbecontrolled by negative reinforcement in escape contingencies with humans; andb)whether the observed levels of variability may be a function of the levelsofrequirement to vary, and whether such levels are affected by the order of exposure(i.e., increasing and decreasing). For this, a total of 26 participants was divided intotwoexperiments. Units of four mouse click responses in two squares on a computer screenshould be emitted in order to end 3.000Hz and 90dB sound stimuli (escape responses). In Experiment I, eight participants responded under the following conditions: PhaseLag 0 (CRF) in which all units were reinforced, Phase Lag 5 in which units werereinforced if they differed from the previous five, and Yoked in which the distributionof reinforcements was coupled to what occurred in Phase Lag 5. In Experiment II, 18participants were distributed into three conditions: Crescent (CC): Lag 0, Lag 2, Lag5and Lag 8; Decrescent (DC): Lag 8, Lag 5, Lag 2 and Lag 0; and Decrescent Conditionwith Baseline in Lag 0 (CD0). Data obtained in Experiment I indicate that theprocedure produced and controlled behavioral variability. Most participants variedmore in Lag 5 (in which variation is required) when compared to Lag 0 (CRF) andYoked, in which there was no variation requirement. Data obtained in the Experiment Ireplicate and extend to aversive control the production and control of variabilityincontingencies of negative reinforcement with escape responses. In Experiment II, thedata were more diverse and suggest that more studies are needed for conclusivestatements. In CC, one participant increased the variation with the increase of therequirement and another reached variation rates in Lag 8; in CD, in general, thevariability index are higher and there is greater variability in Lag 5; In CD0, for oneparticipant, greater variability occurs in the greatest demands and one had levels that ofvalues considered to be variable